Humanistic Education and the Concept of "Merdeka Belajar" in Indonesia: A Perspective of the Qur'an - Ahmad Mujahid; Andi Aderus; Mirnawati Mirnawati; Firman Firman (AL-ISHLAH: Jurnal Pendidikan, 2022)
The discourse on the concept of "Merdeka Belajar" in the education system in Indonesia is still an exciting topic for discussion. One of the topics that become a question is whether the concept of "Merdeka Belajar" is in line with the concept of education that humanizes humans from the perspective of the Qur'an. This literature study aims to reveal and describe the concept of education that humanizes humans and its relevance to the concept of 'Merdeka Belajar,' which is currently applied in the education system in Indonesia based on the perspective of the Qur'an. The data were obtained through a literature review where the procedures and steps referred to several verses in the Qur'an relevant to the topic of discussion. The verses that are the subject of study in this paper include Al-Isra: 70, al-Mujādilah: 11: Al-Nahl: 125, An-Nisa": 1, and al-Hujurat: 13. Furthermore, the verses of the Qur "an are analyzed using the thematic methods (maudhu "i) with content analysis techniques. The results conclude that education is essential for human life; it can shape people and determine their social status. Education humanizes humans by understanding each individual as a natural human being. Therefore, it was in line with the concept of "Merdeka Belajar" which gives freedom to each individual to choose education to actualize himself.